Postnatal Midwifery Care Management For Mrs. "N" With Breast Milk Engorgement at Bara-baraya Healt Center Makassar on August 4, 2022: Manajemen Asuhan Kebidanan Post Natal pada Ny "N" dengan Bendungan Asi di Puskesmas Bara-Baraya Kota Makassar Tanggal 4-24 Agustus Tahun 2022 - Sulfiana; Anieq Mumthi’ah Al Kautzar; Ferawati Taherong (Jurnal Midwifery, 2024)
Breast Milk engorgement is breast milk that is not immediately released causing blockage in the veins and lymphatic vassels, which result in obstructed milk flow pressure on the mother’s milk ducts, leading to increased blood and lymphatic flow that causes breast swelling. This research aims to provide midwifery care to Mrs. “N” on her third day postpartum with breast milk engorgement using the seven-step varney midwifery care approach and documenting it in SOAP format. The result of the case study on Mrs. “N” show no difficulties in managing the case. The midwifery care menegement given to Mrs. “N” with breast milk engorgement was such as giving education on breast care, proper breastfeeding technique and positioning, and giving 500 mg paracetamol as an analgetic (pain reliever). In conclusion, the care provided is successful with no implications found in the mother, and the mother’s condition improved as indicated by her breast returning to normal and the baby actively breastfeeding.